Microwave-assisted extraction of essential oils from basil leaves (Ocimum basilicum L.) and coriander seeds (Coriandrum sativum L.): A comparative study on chemical composition, antioxidant capacity and antimicrobial activity - G.M. Masud Rana; Subarna Sandhani Dey; Bijoy Chandra Ghos; Md. Jasim Uddin; Tahmina Akter Chowdhury; Md. Tariqul Islam; Toufikur Rahman; Md. Jobayear Hossain; Jaytirmoy Barmon; Mst. Sarmina Yeasmin (Applied Food Research)
Essential oils (EOs), known for their aromatic and bioactive properties, are widely utilized in the cosmetic and food industries. Microwave-assisted extraction (MAE) has emerged as a green, efficient and rapid technique for extracting EOs from plant sources. This study focused on extracting EOs from Ocimum basilicum L. leaves (OBLEO) and Coriandrum sativum L. seeds (CSSEO) collected from northern Bangladesh using MAE and comparing their physicochemical properties, antioxidant capacity, and antimicrobial activities. Gas chromatography-mass spectrometry (GC–MS) analysis identified linalool as a major common component in both essential oils, comprising 58.50 % in CSSEO and 20.71 % in OBLEO. Where estragole (35.70 %), anise camphor (35.25 %), and linalool (20.71 %) were the predominant constituents in OBLEO, and linalool (58.50 %), α-pinene (13.37 %), and γ-terpinene (7.52 %) were main components of CSSEO. Fourier-transform infrared (FTIR) spectroscopy confirmed the presence of functional groups such as C–H, C = C, OH, and C = O, indicative of alkanes, alkenes, alcohols, and carbonyl compounds. In DPPH antioxidant assays, OBLEO exhibited higher activity (IC50 =12.999 ppm) compared to CSSEO (IC50 = 15.002 ppm). Antimicrobial efficacy, evaluated through zone of inhibition (ZOI) and minimum inhibitory concentration (MIC), demonstrated that CSSEO had the strongest antibacterial activity against Escherichia coli (ZOI: 23.5 mm, MIC: 3.9 µL/mL), followed by Staphylococcus aureus and Pseudomonas aeruginosa. Conversely, OBLEO showed notable antifungal activity against Candida albicans (ZOI: 20.7 mm, MIC: 3.9 µL/mL). The findings demonstrate significant differences in yield, composition, and biological activities, offering insights into the potential uses of these essential oils in food, pharmaceutical and cosmetic industries.